Profitability and yield gap between research station and farm level of Binamoog-8 - Islam, Syful; Chanda, Mangal Chandra; Haque, Mohammad Rashidul; Sultana, Razia; Yunus, Muhammad (Asian Journal of Medical and Biological Research, 2017)
Estimating profitability and yield gap between research station and farm level of Binamoog-8 was conducted in five major Binamoog-8 growing areas of Bangladesh, namely Ishwardi, Magura, Natore, Jessore and Meherpur. The average cost of production in farm level of Binamoog-8 is Tk. 47373.55ha-1 and higher in Ishwardi (Tk. 53454.92 ha-1) followed by Meherpur, Magura, Natore and Jessore of Tk. 45160.28, Tk. 44300.14, Tk. 45232.95 and Tk. 48719.47 per hectare, respectively .The major shares of total cost were human labour, power tiller and irrigation. The net returns were Tk. 41160, Tk. 42902.30, Tk. 53603.18, Tk. 47494.60 and Tk. 40437.16 per hectare followed in Ishwardi, Meherpur, Magura, Natore and Jessore, respectively. The highest net return (Tk. 53603.18 ha-1) comes from Magura district for Binamoog-8.The undiscounted average benefit cost ratio over full cost basis were 1.77, 1.95, 2.21, 2.05 and 1.83 for Binamoog-8 in field level for Ishwardi, Meherpur, Magura, Natore and Jessore, respectively. The average yield gap of Binamoog-8 in farm level and research station was 129.05 kg per hectare. The yield gap between research station and farm level were 102.97 kg, 185.50 kg, 45.85 kg, 128.50 kg and 182.45 kg per hectare for Binamoog-8 in Ishwardi, Meherpur, Magura, Natore and Jessore, respectively. The highest yield gap between research station and field level was in Meherpur (185.50 kg per hectare) and lowest in Magura (45.85 kg per hectare). Farmers were facing various constraints in Binamoog-8 cultivation. Different strategies, such as lack of quality seed and fertilizer in appropriate time, lack of credit facilities, rainfall during germination period, insect infestation and pathogen infection, pod maturity in different times have been discussed as strategies to minimize yield gaps. Asian J. Med. Biol. Res. December 2016, 2(4): 685-688